Wearable Power‐Textiles by Integrating Fabric Triboelectric Nanogenerators and Fiber‐Shaped Dye‐Sensitized Solar Cells. Issue 20 (19th July 2016) - Pu, Xiong; Song, Weixing; Liu, Mengmeng; Sun, Chunwen; Du, Chunhua; Jiang, Chunyan; Huang, Xin; Zou, Dechun; Hu, Weiguo; Wang, Zhong Lin
Abstract : Textile‐based energy harvesting is realized by integrating fabric triboelelctric nanogenerator and fiber‐shaped dye‐sensitized solar cell to scavenge the energy of human motion and solar energy, respectively. The hybrid power‐textile is demonstrated to be soft, flexible, wearable, and promising for applications in wearable electronics or smart textiles.